Real-world safety profile of alectinib: a 10-year pharmacovigilance study based on the FDA adverse event reporting system - Le Zhang; DanDan Li; ChenJing Luo; Li Fan; Min Hu; Fei Ye; Peng Gu (Frontiers in Medicine, 2026)
Objective Alectinib is the standard first-line therapy for treatment-naïve ALK-positive non-small cell lung cancer (NSCLC). Given its increasing clinical utilization, a comprehensive pharmacovigilance evaluation of its adverse events (AEs) is warranted. Methods We assessed alectinib-associated AEs using the FDA Adverse Event Reporting System (FAERS) database from Q4 2015 to Q3 2025. AEs were categorized per MedDRA, and four disproportionality analysis algorithms were used to detect potential safety signals. Results A total of 8,602 reports with alectinib as the primary suspect drug were included. Overall, 51.1% were serious adverse events (SAEs). Median AE onset was 120 days (IQR: 27–428), with 27.4% within 30 days and 28.9% after 360 days. All algorithms identified 108 preferred terms meeting positive safety signal criteria. Besides well-recognized AEs, novel signals emerged: hypertriglyceridemia, hypercholesterolemia, pericardial effusion, erythema multiforme, muscle fatigue, and myositis. Multivariate regression showed male sex and age ≥65 years were independently linked to higher SAE risk. Conclusion Leveraging a large pharmacovigilance database, this study comprehensively characterized alectinib's safety profile. It confirmed established signals and uncovered novel potential AEs needing further prospective research. Subgroup disparities and key monitoring windows were identified, deepening mechanistic understanding and supporting optimized clinical risk mitigation strategies. It should be noted that disproportionality analysis is used to detect potential safety signals rather than establishing causal relationships, and all identified signals require further clinical evaluation.